Bibliometric Visualisation of Research Performance of Post COVID -19 and Mucormycosis: Where Do We Stand? - Mallikarjun, Kappi; B, Mallikarjun; T, Vidyashree (Journal of Drug Delivery and Therapeutics, 2021)
Purpose: The second wave of the covid-19 pandemic has impacted global healthcare tremendously and mucormycosis associated with coronavirus disease is one of the deadly fungi that hit India in April 2021. An increasing number of research papers are upcoming with mucormycosis associated with coronavirus research and this paper aims at performing a bibliometric visualisation of all the available research on post covid-19 and mucormycosis. Method: The Scopus database was selected and the search query (ALL (novel coronavirus 2019 OR coronavirus 2019 OR COVID 2019 OR COVID 19 OR nCOV OR SARSCoV2 OR COVID19) and (black fungus or white fungus or yellow fungus or mucormycosis) was developed on 25 May 2021 to retrieve all the bibliographic records on the domine of interest. VOSviewer software tool was used to constructing and visualising bibliometric networks to measure co-authors, countries, and institutions document citation, keyword metrics. Results: A total of 154 documents were retrieved in the search, these were authored by 3,806 authors and published in 133 sources (journals, books, etc.). USA, India, and UK ware contributed the highest papers. Journal of Fungi (4), Heliyon (3), International Journal of Molecular Sciences (3), and Phytotherapy Research (3) are the journals that published the highest papers. Author per document was 24.7; Documents per author were 0.0405 and collaboration index was marked 26.5 during the period. Conclusion: this bibliometric visualisation presents the qualitative and quantitative metrics for post-covid-19 and mucormycosis research and provides evidence that research in this domine is more in-depth than before. It is hoped that this well-directed research in different countries will provide new avenues for understanding diseases caused by mucormycosis associated with coronavirus. Keywords: Bibliometric Visualisation; Post-Covid-19; Mucormycosis; Annual Growth Rate; Research Performance; India